2018
DOI: 10.1590/1518-8345.1812.2944
|View full text |Cite
|
Sign up to set email alerts
|

Direct costs of integrated procedures of conventional hemodialysis performed by nursing professionals

Abstract: Objective:to analyze the mean direct cost of the constituent procedures of conventional hemodialysis, performed in three public teaching and research hospitals. Method:quantitative, exploratory-descriptive study, of the multiple case study type. The mean direct cost was calculated by multiplying the time (timed) spent by nursing professionals, on the execution of procedures, by the unit cost of direct labor, added to the cost of materials and solutions/medications. Results:the total mean direct cost, in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…In this context, the increased costs with material resources has attracted the attention and concern of health managers, who need to promote investments in resource management systems, in order to generate less burden and to maintain the quality and quantity of care. 21 In this perspective, a study 22 that investigated the panoramic situation of HD carried out by the public health system in Brazil revealed that almost 50% of the spendings with renal therapy in the country were concentrated in São Paulo, Rio de Janeiro and Minas Gerais. Such data also reflect the unequal treatment between the regions of the country, registered in another national study .…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the increased costs with material resources has attracted the attention and concern of health managers, who need to promote investments in resource management systems, in order to generate less burden and to maintain the quality and quantity of care. 21 In this perspective, a study 22 that investigated the panoramic situation of HD carried out by the public health system in Brazil revealed that almost 50% of the spendings with renal therapy in the country were concentrated in São Paulo, Rio de Janeiro and Minas Gerais. Such data also reflect the unequal treatment between the regions of the country, registered in another national study .…”
Section: Methodsmentioning
confidence: 99%
“…As the execution of a procedure may require the consumption of different quantities of supplies, it is possible to establish the average direct cost [ C(Pi)true¯ ] from the average direct cost of the set of materials [ C(Pi)mattrue¯ ] , solutions [ C(Pi)soltrue¯ ]  and workforce [ C(Pi)mobtrue¯ ] 7 : C(Pi)true¯=C(Pi)mattrue¯+C(Pi)soltrue¯+C(Pi)mobtrue¯ (equation 1).…”
Section: Methodsmentioning
confidence: 99%
“…The C(Pi)mobtrue¯ is obtained by the sum of the average costs of each professional category (nurses and nursing technicians) [Chc true¯] participating in the procedure 7  C(Pi)mobtrue¯=true140%c=1nChctrue¯ (equation 8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations